A thematic study of Islamic perspectives in scopus indexed articles. Implications on medical imaging - Zainuddin, Zainul Ibrahim (University of Nebraska-Lincoln, 2015)
Discussions pertaining to the various Islamic dimensions are actively being undertaken in the media. Within the academic circle, journal articles are accepted as an effective media in the dissemination of knowledge. Articles with Islamic perspectives can be found in disciplines that include Medicine, Banking, Economics and Finance. However, there is little to suggest of the types and frequencies of Islamic perspectives in Medical Imaging. This paper attempts to fill the gap. The methodology involves the use of Scopus database and its interactive search facility. The justification of using Scopus is the user-friendliness of its search interface and the ability to perform off-line analysis via the CSV (Comma Separated Value) facility that permits the resultant data to be appreciated on an Excel spreadsheet. With nearly 55 million documents, including 100 percent coverage by Medline, the data extracted from Scopus is taken as a general representation of Islamic perspectives in literature. Twenty-seven Islam related terms were used to represent Islamic perspectives. A general survey involving all subject areas as well as a specific study involving Medical Imaging were conducted. The results suggest minimal representation of articles with Islamic perspectives in Scopus. Discussions on the implications of the results and proposals to alleviate the situation upon the Muslim Medical Imaging practitioner are given.